Diagnositic value of pelvic enthesitis on MRI of the sacroiliac joints in enthesitis related arthritis. Issue 1 (December 2015) - Herregods, N.; Dehoorne, J.; Pattyn, E.; Jaremko, J.; Baraliakos, X.; Elewaut, D.; Vlaenderen, J; Bosch, F.; Joos, R.; Verstraete, K.; Jans, L.
Abstract Background To determine the prevalence and diagnostic value of pelvic enthesitis on MRI of the sacroiliac (SI) joints in enthesitis related arthritis (ERA). Methods We retrospectively studied 143 patients aged 6–18 years old who underwent MRI of the SI joints for clinically suspected sacroiliitis between 2006–2014. Patients were diagnosed with ERA according to the International League of Associations for Rheumatology (ILAR) criteria. All MRI studies were reassessed for the presence of pelvic enthesitis, which was correlated to the presence of sacroiliitis on MRI and to the final clinical diagnosis. The added value for detection of pelvic enthesitis and fulfilment of criteria for the diagnosis of ERA was studied. Results Pelvic enthesitis was seen in 23 of 143 (16 %) patients. The most commonly affected sites were the entheses around the hip (35 % of affected entheses) and the retroarticular interosseous ligaments (32 % of affected entheses). MRI showed pelvic enthesitis in 21 % of patients with ERA and in 13 % of patients without ERA. Pelvic enthesitis was seen on MRI in 7/51 (14 %) patients with clinically evident enthesitis, and 16/92 (17 %) patients without clinically evident enthesitis. In 7 of 11 ERA-negative patients without clinical enthesitis but with pelvic enthesitis on MRI, the ILAR criteria could have been fulfilled, if pelvic enthesitis on MRI was included in the criteria. There is a high correlation between pelvic enthesitis and sacroiliitis, with sacroiliitis present in 17/23 (74 %) patients with pelvic enthesitis. Conclusions Pelvic enthesitis may be present in children with or without clinically evident peripheral enthesitis. There is a high correlation between pelvic enthesitis and sacroiliitis on MRI of the sacroiliac joints in children. As pelvic enthesitis indicates active inflammation, it may play a role in assessment of the inflammatory status. Therefore, it should be carefully sought and noted by radiologists examining MRI of the sacroiliac joints in children.